The Impact of Internal Communication on Organizational Performance Efficiency - Alharbi, Saleh Hamed (The Arab Journal of Administration, 2025)
Mature organizations become aware about the importance of Communication systems because it is one of crucial factors that contribute for improving and raising performance in organizations. Where internal communication systems play a critical role for building a culture for the organizations that link their employees with their organizations. This study aims to evaluate the relationship between internal communication systems and its impact on performance efficiency on organizations at the University of Tabuk- KSA. This study used quantitative methodology, where the survey method and the non-probability sampling approach were applied. The sample size was 286, and questionnaires were distributed online. The result of this study found there is a positive relationship between Communication Systems and Human Resource Management (HRM). Besides, a positive relationship between HRM and internal Communication. The study further unveiled the mediator role internal Communication of the relationship between Communication Systems and Efficiency. The study concluded that there is a negative relationship between Communication Systems and Performance Efficiency. The results of this study contribute to the knowledge by uncover the latent factors that lead to increase the efficiency of performance in organizations, and it also represents a contribution to decision makers on the importance of developing internal communication to reach better institutional performance.